Analisis dan Perancangan Aplikasi E-Meeting Berbasis Web - Yen Lina; Sebastian Karuna Alfasan (Bina Nusantara University, 2013)
Information technology is closely related to wide area networks. BINUS University pays much attention to the development of information technology. Yet, it has not applied all concepts of information technology. There are still activities carried out conventionally such as meeting activity. This is the main attraction of the authors to implement a new system. The purpose of this research is to analyze and design an e-meeting application of Computer Science Department of BINUS University. By using this application, user will be easyto conduct meeting without location barrier. This research is using analysis method on literacy study, as well as analysis on current meeting process through interview with expert and user to detect current problem. Design method usies software engineering concept, by Unified Modeling Language and Entity Relationship Diagram. UML notation explains the overview and the detail of e-meeting system. Relational database explains data structure used in this system. The result of this research is a development of e-meeting web based application to help improve meeting activity to be more effective and efficient. E-meeting application has many helpful features as used in regular meeting, as well as administration panel to control and manage user of this application.